Komunikasi Non Verbal Ustaz Lukmanulhakim Dalam Kajian Fikih Mingguan - Fuadi, Al-kindi Nur; Ridwan, Aang; Nur Chidayah, Prita Priantini (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to understand Ustaz Lukmanulhakim's facial kinesics, gestural kinesics and postural kinesics in delivering material on fiqh studies at the Al-Jihad Mosque. The theory used is the Kinesics theory. This research uses a qualitative descriptive method using interview, observation and documentation techniques. The research results show that Ustaz Lukmanulhakim's nonverbal communication in the study of jurisprudence at the Al-Jihad Mosque is divided into three aspects, namely facial kinesics showing facial expressions, interaction and enthusiastic eye gaze. Gestural kinesics shows the use of hand language, hand positions, and head movements. Postural kinesics shows Ustaz Lukmanulhakim's body and shoulder posture, distance and whole body movement.